The Role of the Office of Religious Affairs in Central Mawasangka District, Central Buton Regency, in Addressing Early Marriage - Usaimin, M. AL –; Miro, Abbas Baco; Billah, Muktashim (JURNAL MAHASISWA YUSTISI, 2025)
This study explores the role of the Office of Religious Affairs (Kantor Urusan Agama/KUA) in Central Mawasangka District, Central Buton Regency, in preventing early marriage. Early marriage remains a significant social and legal issue in several regions of Indonesia, including Southeast Sulawesi, due to factors such as cultural traditions, economic hardship, and limited access to education. The research applies a qualitative descriptive method, using interviews, documentation, and library research to analyze the preventive strategies implemented by KUA officials. Findings indicate that the KUA plays a strategic role not only in administering marriage registration but also in providing premarital counseling, community education, and coordination with local government agencies. The study also reveals several obstacles, including deeply rooted cultural norms, lack of awareness among parents, and limited resources for outreach programs. Nevertheless, the proactive engagement of KUA in socialization campaigns, religious lectures, and policy advocacy has contributed to a gradual reduction in early marriage cases. This study concludes that strengthening institutional capacity, enhancing inter-agency collaboration, and increasing public awareness are essential to achieving sustainable prevention.